Measurement of Ultrashort Laser Pulse Width in a Wide Spectrum Range Using Dimethyl Sulfoxide by Optical Kerr Effect Technique - 孔德贵 常青 叶红安 高亚臣 张立欣 王玉晓 张学如 杨昆 宋瑛林 (Chinese physics letters, 2010)
We illustrate that applying the optical Kerr effect technique to dimethyl sulfoxide （DMSO） can determine the width of laser pulses in a wide spectrum range that is transparent. Different from many other simple molecular liquids, such CS2, and toluene, DMSO responds to both 130 fs 800 nm laser pulses and 248 fs 400 nm laser pulses with electronic motions only. Therefore, the observed signal as a function of time reflects the temporal distribution of the intensity. We verify our illustration by both the autocorrelation technique and spectra analysis.